2021
DOI: 10.7717/peerj.10615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mixing two legume species at seedling stage under different environmental conditions

Abstract: While intercropping is known to have positive effects on crop productivity, it is unclear whether the effects of mixing species start at the early plant stage, that is, during germination. We tested whether the germination of two legume species, alsike clover and black medic, characterized by a contrasting response to water availability and temperature is affected by mixing. We set up four experiments in each of which we compared a 1:1 mixture against the two monocultures, and combined this with various other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…higher relative SW emergence in mixtures compared to monocultures. It may be assumed that the higher SW emergence in mixtures was due to the temporal complementarity effect in resource use between SW and FB (Li et al, 2016;Xiao et al, 2018) in the very early stage of plant development (Elsalahy et al, 2021). In our eld experiment, we observed that FB was slower to germinate than SW, potentially because of the (necessarily) deeper seed depth of FB (6 cm) than of SW (3 cm).…”
Section: Mixture Effects At the Early Development Stagementioning
confidence: 55%
See 3 more Smart Citations
“…higher relative SW emergence in mixtures compared to monocultures. It may be assumed that the higher SW emergence in mixtures was due to the temporal complementarity effect in resource use between SW and FB (Li et al, 2016;Xiao et al, 2018) in the very early stage of plant development (Elsalahy et al, 2021). In our eld experiment, we observed that FB was slower to germinate than SW, potentially because of the (necessarily) deeper seed depth of FB (6 cm) than of SW (3 cm).…”
Section: Mixture Effects At the Early Development Stagementioning
confidence: 55%
“…The relative emergence of SW was 16.4% higher than FB (Table 6) at that stage, indicating dominance, but the PEER value of FB (0.51 at LD and 0.50 at HD; Table 6) showed no reduction of FB emergence in the mixture compared to FB monoculture. The higher emergence of SW in the mixture than in the SW monoculture was observed presumably due to the complementarity effect (Xiao et al, 2018), and could be linked to asynchronous germination between the two species (Elsalahy et al, 2021). At the same time, the observed dominance of SW did not lead to the suppression of FB emergence in the mixture possibly due to the small size of the cereal, and the short time of co-growth between the two species.…”
Section: Dependence Mixture On Cultivar Identity Environment and Densitymentioning
confidence: 85%
See 2 more Smart Citations
“…However, as plant traits differ in different life history stages, the form, intensity and mechanism of interspecific interactions may change with the ontogenetic process of plants [10][11][12]. Researchers have recognized the importance of regeneration on community assembly and investigated some adult-to-seed and seed-toseed interactions in recent years [13][14][15], but our understanding of interspecific interaction mechanisms during early life history stage of plants (i.e., germination) is still limited.…”
Section: Introductionmentioning
confidence: 99%